Excitotoxic lesion of the posterior part of the dorsal striatum does not affect the typically dopaminergic phenomenon of latent inhibition in conditioned taste aversion. (February 2015) - Molero-Chamizo, Andrés
Highlights: Lesion of the posterior part of the dorsal striatum does not interfere with neophobia. Latent inhibition of CTA is not disrupted by lesion of the posterior dorsal striatum. The posterior dorsal striatum is not necessary for latent inhibition of CTA. Abstract: The stimulation or blockade of dopaminergic activity interrupts or increases, respectively, the phenomenon of latent inhibition in different paradigms. Furthermore, the involvement of the nucleus accumbens in latent inhibition has been demonstrated in several learning paradigms, including conditioned taste aversion. However, the role of the dorsal striatum in the pre-exposure effect on the acquisition of taste aversion remains unclear. In order to determine whether this region of the striatum is a structure necessary for latent inhibition of conditioned taste aversion, excitotoxic lesions were made in the posterior part of the dorsal striatum of Wistar rats. Subsequently, half of the animals was pre-exposed to the flavor, and the magnitude of the taste aversion was compared to that of sham animals pre-exposed and non-pre-exposed to the same flavor. The results showed that the excitotoxic lesion in this area of the dorsal striatum, compared to sham animals, left latent inhibition of the conditioned taste aversion intact. These data suggest that the posterior part of the dorsal striatum is not necessary for the acquisition of latent inhibition, at least in the conditioned taste aversion paradigm.